LITERARY ENVIRONMENT IN KOKAND AND METHODOLOGY OF THE STUDY OF MUKIMI’S (Academia Science Repository, 2023)
In this article literary environment in Kokand and methodology of the study of Mukimi’s creative works in the late XIX and early XX centuries developed. They are as follows: 1) Fair determination of the relationship between the socio-historical environment and the poet; 2) Selection of adequate criteria for assessing the creative outlook of the literary heritage; 3) The authenticity of literary interpretations; 4) The influence of creative works on the progress of literary-aesthetic thought in today's globalization.